Arterial pharmacokinetics in a patient-specific atherosclerotic artery-a simulation study - Biswas, Sayantan; Sarifuddin, -; Mandal, Prashanta Kumar (GANIT: Journal of Bangladesh Mathematical Society, 2021)
Of concern in the paper is a numerical study of endovascular drug delivery in a patient-specific atherosclerotic artery through a mathematical model in which the luminal flow is governed by an incompressible vis- cous Newtonian fluid, and the transport of luminal as well as tissue concentration is modeled as an unsteady convection-diffusion process. An image processing technique has been successfully adopted to detect the edges of the computational domain extracted from an asymmetric (about the centerline of the artery) patient-specific atherosclerotic artery. Considering each pixel as a control volume, the Marker and Cell (MAC) method has been leveraged to get a quantitative insight of the model considered by exploiting physiologically realistic initial, boundary as well as interface conditions. Simulated results reveal that the number as well as the length of separation zone does increase with increasing Re, and the near-wall velocity contour might be important for estimating the near-wall residence time for the pool of drug molecules available for tissue uptake. Results also show that the more the tissue porosity and interface roughness do not necessarily imply the more the effective- ness of delivery, even though they enhance the averaged concentration in the tissue domains, and also the area under concentration diminishes with increasing Peclet number. Thus, the tissue porosity, the Peclet number and various geometrical shapes (interface roughness) play a pivotal role in the dispersion and the effectiveness of drug delivery. GANITJ. Bangladesh Math. Soc.41.1 (2021) 62-77